Development of fetal surgery in Ecuador, collaboration between health care and academia, a good practice - Nieto Castro, Belén (2024)
In Ecuador, approximately 250,000 children are born every year. In 2022, therewere 1,609 deaths of children under one year of age. Of these deaths, 21.5%were due to congenital anomalies, occupying second place among the ten leadingcauses of mortality. This reality of fetal, neonatal and infant health has beenechoed by international organizations that urge countries to strengthen the timelydiagnosis of congenital defects, relying on technological advancement, training ofhuman resources and investment in areas of care of the fetus as a patient, takinginto account that some of these defects can be treated in prenatal life, reducingsequelae, and improving the quality of life. In response to these needs, in Ecuadoragreements were generated between the University-Academy, Ministry of PublicHealth-Assistance and private groups dedicated to continuing education, to jointlydevelop a sustainable fetal health program that benefits fetuses that are carriers ofpathologies. In this paper we describe one of the arms of this project that is relatedto the care of fetuses that can benefit from the advancement of fetal surgery inEcuador.